A preliminary study of noise exposure among grass cutting workers in Malaysia - Tengku Ismail, Tengku Hanidza; M. Jan, Amirah A.; Abdullah, Ramdzani; Ariff, Madinah (Elsevier, 2013)
The purpose of this study is to determine noise exposure among grass cutters. Eighteen grass cutters were monitored for 8 hours each, using the Noise dose meter. The workers were exposed to noise levels ranging from 84.3 dB(A) to 92.3 dB(A), TWA (mean 88.0 dB(A). The Lmax value ranged from 100.4 dB(A) to 126.5 dB(A) (mean 109.5 dB(A)). 27.8% workers exceeded the permissible level 90 dB(A), and 83.3% exceeded the action level 85 dB(A). Audiometric test for both ears showed some evidence of mild to moderate hearing impairment in some workers (5 out of 18). This study revealed that some workers were exposed to excessive noise level and were at risk of acquiring noise induced hearing loss.